Importance of anchor genomes for any plant genome project - Messing, Joachim (The National Academy of Sciences, 1998)
Progress in agricultural and environmental technologies is hampered by a slower rate of gene discovery in plants than animals. The vast pool of genes in plants, however, will be an important resource for insertion of genes, via biotechnological procedures, into an array of plants, generating unique germ plasms not achievable by conventional breeding. It just became clear that genomes of grasses have evolved in a manner analogous to Lego blocks. Large chromosome segments have been reshuffled and stuffer pieces added between genes. Although some genomes have become very large, the genome with the fewest stuffer pieces, the rice genome, is the Rosetta Stone of all the bigger grass genomes. This means that sequencing the rice genome as anchor genome of the grasses will provide instantaneous access to the same genes in the same relative physical position in other grasses (e.g., corn and wheat), without the need to sequence each of these genomes independently. (i) The sequencing of the entire genome of rice as anchor genome for the grasses will accelerate plant gene discovery in many important crops (e.g., corn, wheat, and rice) by several orders of magnitudes and reduce research and development costs for government and industry at a faster pace. (ii) Costs for sequencing entire genomes have come down significantly. Because of its size, rice is only 12% of the human or the corn genome, and technology improvements by the human genome project are completely transferable, translating in another 50% reduction of the costs. (iii) The physical mapping of the rice genome by a group of Japanese researchers provides a jump start for sequencing the genome and forming an international consortium. Otherwise, other countries would do it alone and own proprietary positions.